2006
DOI: 10.1007/s10875-006-9025-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety and Tolerability of a New 10% Liquid Intravenous Immune Globulin [IGIV 10%] in Patients with Primary Immunodeficiency

Abstract: The present clinical study was designed to evaluate the efficacy, pharmacokinetics and safety of a new 10% liquid intravenous immune globulin in patients with primary immunodeficiency diseases. Sixty-one adults and children with primary immuno-deficiency diseases received doses of 300-600 mg/kg body weight every 21-28 days for 12 months. No validated acute serious bacterial infections were reported. The 95% confidence interval for the annualized rate of acute serious bacterial infections (primary endpoint) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
39
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 18 publications
19
39
0
1
Order By: Relevance
“…The study met its primary efficacy endpoint with an annual aSBI rate of 0.08. This rate is comparable to the rates recently observed with other IVIG preparations in patients with PID [19][20][21]. Furthermore, the annual rate of any infection (3.55, including aSBI) reported in this study is consistent with annual infection rates in other published reports [20][21][22].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The study met its primary efficacy endpoint with an annual aSBI rate of 0.08. This rate is comparable to the rates recently observed with other IVIG preparations in patients with PID [19][20][21]. Furthermore, the annual rate of any infection (3.55, including aSBI) reported in this study is consistent with annual infection rates in other published reports [20][21][22].…”
Section: Discussionsupporting
confidence: 91%
“…However, based on clinical experience, a target serum IgG trough level of at least 5 g/L has been proposed in the literature for IVIG therapy, with even further protection achieved at levels of 9 g/L and higher [24][25][26][27]. Mean serum IgG trough concentrations remained between 8.84 and 10.27 g/L over the course of this study, comparable to trough levels reported in other recent studies [19][20][21][22].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…24 The effi cacy of Privigen as shown in this study (annual rate of aSBI of 0.11 per patient; 99% CI 0.369) was comparable to that of other liquid IVIG preparations tested recently in mixed pediatric and adult patient populations with PID. 18,[27][28][29] Prior studies reporting effi cacy and safety of IVIG products have not reported specifi c rates of aSBI in pediatric patients, nor have declared the proportion of pediatric patients in the study populations. In a study of Flebogamma ® 5% performed in 51 patients aged 14-74 years, the rate of aSBI was 0.061 per patient per year (upper 1-sided 99% CIs of 0.183).…”
mentioning
confidence: 99%
“…29 In 61 adults and children (6-72 years) treated with GAMMAGARD LIQUID 10%, no aSBIs occurred during the 12-month period of the study (upper 1-sided 95% CIs of 0.060 per patient per year). 27 In a trial comparing effi cacy of Gamunex ® 10% and Gamimmune ® N, 9 of 73 (12%) patients treated with Gamunex 10% for 9 months experienced aSBIs resulting in a rate of <0.2 per year. 18 This study documents for the fi rst time effi cacy and safety of an IVIG product in pediatric patients with PID.…”
mentioning
confidence: 99%